1997
DOI: 10.1038/sj.ejcn.1600446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing breast milk docosahexaenoic acid on plasma and erythrocyte phospholipid fatty acids and neural indices of exclusively breast fed infants

Abstract: Objectives: To determine the effect of increasing docosahexaenoic acid (DHA, 22 : 6 n-3) in breast milk on infant fatty acid pro®les. A secondary aim was to examine aspects of neural development. Design and Setting Double blind, placebo controlled study of infants recruited from postnatal wards at Flinders Medical Centre. Subjects: Fifty-two healthy term infants who were breast fed for at least 12 weeks and were from middle class families. Intervention: Breast milk with DHA concentrations that ranged from 0.1±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
151
3
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(167 citation statements)
references
References 17 publications
11
151
3
2
Order By: Relevance
“…This had no apparent effect on the problem solving ability of the infants at nine month of age, although it seemed to have a positive effect in girls. A previous maternal-supplementation trial found that a similar increase in breast-milk DHA was associated with a positive effect on the Bayley mental development index score at one year of age, which was no longer evident at two years [25]. A recent Norwegian study has shown that supplementation with cod liver oil during pregnancy and lactation resulted in an increased mental processing score at four years of age [26].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This had no apparent effect on the problem solving ability of the infants at nine month of age, although it seemed to have a positive effect in girls. A previous maternal-supplementation trial found that a similar increase in breast-milk DHA was associated with a positive effect on the Bayley mental development index score at one year of age, which was no longer evident at two years [25]. A recent Norwegian study has shown that supplementation with cod liver oil during pregnancy and lactation resulted in an increased mental processing score at four years of age [26].…”
Section: Discussionmentioning
confidence: 96%
“…Small cross sectional studies have observed relationship between the DHA-content of human milk, or levels of DHA in infant or maternal plasma, and the sleep pattern, visual acuity, cognitive abilities, speech perception and language development of breast-fed infants [14,15,[20][21][22][23][24]. Furthermore, studies supplementing lactating mothers with marine oils have shown that the DHA-intake of breast-fed infants may have beneficial effects on mental development [25][26][27]. The present maternal post-natal FO-supplementation trial was performed in Denmark where the population has a high intake of marine fatty acids compared to that in many other Western countries [35] and thus, higher levels of breast-milk DHA [1].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to LA, the levels of DHA in human milk also vary widely within and among populations (Innis, 1992(Innis, , 2004, which again results in differences in the plasma and cell membrane levels of DHA among breast-fed infants (Gibson et al 1997;Innis & King, 1999;Jensen et al 2000;Innis et al 2001). Milk fat from women following vegan diets, which lack DHA, contains < 0 .…”
Section: Maternal Dietary Lipids and Their Effect On The Composition mentioning
confidence: 99%
“…Supplementation of formula-fed preterm infants with graded levels of AA (0-1·1 g/100 g total fat) and DHA (0-0·76 g/100 g total fat) compared with breastfed babies demonstrated that plasma and erythrocyte LCPUFA levels can be mimicked by supplementing formula at similar levels to those present in breast milk. These levels translated into 0·54 g AA and 0·3 g DHA/100 g total fat for omnivorous women (Gibson et al 1997). Most LCPUFA-containing formulas presently used have 0·2-0·4 g DHA and 0·6-0·8 g AA/100 g total fat.…”
Section: Breast Milk As a Reference For The Fatty Acid Composition Ofmentioning
confidence: 99%